Facing the Global Financial Cycle : What Role for Policy. (IMF Working Papers; Working Paper ;, 2021)
Abstract In this paper we ask whether countries can influence their exposure to changes in global financial conditions. Specifically, we show that even though we can model cross-country capital flows via a global factor that closely tracks changes in global financial conditions, there is a large degree of heterogeneity in the sensitivity of each country to this same global factor. We then evaluate whether this cross-country heterogeneity can be attributed to different policy choices, including measures of capital flow management, such as capital controls and macroprudential policies. In our main results, we show that higher levels of capital controls and macroprudential policies both dampen the sensitivity to the global factor. Furthermore, we show that countries' monetary and exchange rate policies can also be successfully deployed. Overall, our results have implications that extend beyond the surge that preceded the 2008 global financial crisis, and that closely resonate in light of the financial disruptions that followed the COVID-19 pandemic.